Downward Communication Model to Improve Employee Performance - Djunaedi, Nandang (International Journal of Psychosocial Rehabilitation, 2020)
Each agency must be able to invite its employees to provide the right form of communication model in accordance with the needs of agencies that can create a person’s performance for the better. This study aims to determine the communication model that influences the performance of an employee in an agency. This research is a descriptive and verification study using simple linear regression analysis, where the respondent population is all employees of industry and foreign trade services in the province of West Java as many as 30 people with a sample of 30 people using SPSS 21 software. The method used in this study is saturation sample technique using the entire population as a sample. Data collection using the direct survey method using a questionnaire. the results of respondents’ responses that have been distributed and the results of testing then communication down affect the performance of employees by 0.787 has a positive and significant effect. To improve employee performance, the authors suggest that there be further research by other researchers regarding the problems of factors that affect employee performance other than downward communication such as security at work, accuracy and appropriateness in payments, organizational conditions and organizational management roles, supervisory ability and quality of work alone. Make improvements to all elements of communication down and employee performance in the future so that abuse or fraud can be avoided.